Ru-catalyzed direct amidation of carboxylic acids with N-substituted formamides. Issue 50 (15th December 2016) - Bi, Xiaojing; Li, Junchen; Shi, Enxue; Wang, Hongmei; Gao, Runli; Xiao, Junhua
Abstract: The direct amidation of carboxylic acids with N -substituted formamides has been accomplished via ruthenium catalysis. In the presence of ruthenium catalyst, a versatile range of carboxylic acids and N -substituted formamides undergoes amidation reaction to produce synthetically useful amides in good yields. CO in amide product came from benzoic acid but not N -substituted formamides, and which was confirmed by Isotope experiment. Graphical abstract: The direct amidation of carboxylic acids with N -substituted formamides has been accomplished via ruthenium catalysis. A versatile range of carboxylic acids and N -substituted formamides undergoes amidation reaction to produce synthetically useful amides in good yields. CO in amide product came from benzoic acid but not N-substituted formamides, and which was confirmed by Isotope experiment.